Landscape Agroecology: Methodologies and Applications for the Design of Sustainable Agroecosystems - Miguel A. Altieri; Clara I. Nicholls; Manuel González de Molina; Angel Salazar Rojas (Land)
Agroecosystem function is related to the positioning of the agroecosystem and its connectivity relationship with the surrounding landscape. Herein, three methodologies are presented, which allow assessment of the links between agroecosystems and the surrounding matrix, yielding information for promoting patterns and mechanisms that foster biodiversity and the provision of multiple ecosystem services such as biological pest control, as well as energy flows and material exchanges. The three methodologies are complementary when assessing agrolandscape-level interactions in situations of regional agroecological transition. Through the use of 11 indicators, a methodology (Assessment of Beneficial Insect Habitat Suitability-ABIHS) was applied in two northern California vineyards to determine whether each agrolandscape provided suitable environmental opportunities to sponsor biological insect pest control. The Main Agroecological Structure [MAS] applied in Chilean family farms elucidates some of the relationships between farms and their biophysical environment, generating data to analyze the links between agroecosystem landscapes, management practices, and insect diversity in family farms. Social Agrarian metabolism (SAM) applied in Spanish agrolandscapes quantifies the biophysical and energy flows in agricultural systems, testing whether such flows are capable of reproducing and/or improving fund elements such as soil, biodiversity, and landscape vegetation in successive production cycles. The three methodologies provide key information for the design of sustainable agroecosystems in the context of an agroecological transition.